Pengembangan Media Pembelajaran Berbasis Android Menggunakan Canva Pada Pembelajaran PAI Materi ''Ayo Sedekah'' Pada Kelas V Di SDN 24 Temmalebba - Rahayu, Putri (Indonesian Journal of Islamic Educational Review, 2024)
This research aims to develop Android-based learning media using the Canva application for PAI learning material "Ayo Sedekah" for VA class. This research is research into the development of the ADDIE (Analysis, Design, Development, Implementation and Evaluation) model. The subjects in this research were students in class VA at SD Negeri 24 Temmalebba. Data collection techniques were carried out using observation, interviews and documentation. The results of this research in the form of research and development produced a product in the form of Android-based learning media using the Canva application for PAI learning with the material "Ayo Sedekah". The stages taken to produce Android-based learning media using Canva are as follows: a) Observation (Analysis) Stage, b) Design Stage, c) Development Stage, and d) Validation Stage. The material in the learning media is about invitations to charity. Based on validation from media experts and material experts, it can be seen that the validation results are categorized as feasible. Overall validation results from material experts and media experts show a good response to the use of Android-based learning media using the Canva application in the learning process.